Pengaruh Public Design, Room Meeting Design Dan Ambience Condition Terhadap Guest Satisfaction Dalam Kegiatan Meeting Di Pangeran Beach Hotel Padang - Febrina Vionicha Milanda; Feri Ferdian (Lembaga Pengembangan Kinerja Dosen, 2023)
This research began with the discovery of problems related to public design, meeting room design, ambience conditions and guest satisfaction. This research aims to analyze the influence of public design, room meeting design and ambience conditions on guest satisfaction in meeting activities at Pangeran Beach Hotel Padang. The population of this study was 300 respondents with a sampling technique using the purposive sampling method. The data collection technique was carried out using a questionnaire which had been tested for validity and reliability using a Likert scale. Hypothesis testing through multiple linear regression testing using SPSS version 25.00 shows that the variables X1, X2 and So hypotheses H1 to H4 are accepted. The public design variable is included in the good category using a master scale of 5 scales with an average value of 4.11. Meeting room design is included in the good category with an average value of 4.26, ambience condition is included in the good category with an average value of 4.26 and guest satisfaction is included in the very good category with an average value of 4.40. The R Square value obtained was 0.73, meaning that the influence of variables X1, X2 and X3 on Y was 73%, while 27% was influenced by other factors.